Soluções singulares para operadores diferenciais parciais com coeficientes constantes - Figueiredo, Elisandra Bär de (2004)
The objective of this work is to present some properties of singular solutions for linear partial differential operators with constant coe±cients. We prove Paley-Wiener-Schwartz s theorem and its version for singular supports, these results carry information about the size of support and singular support, respectively, and also about the regularity of compact support distributions. We also prove two theorems of propagation of singularities s type for solutions of linear partial differential operators with constant coe±cients of real principal type. These results describe in particular, for a very specific situation, how small can the singular support of singular solutions be.